A Proteomic Approach Suggests Unbalanced Proteasome Functioning Induced by the Growth-Promoting Bacterium Kosakonia radicincitans in Arabidopsis - Witzel, Katja; Üstün, Suayib; Schreiner, Monika; Grosch, Rita; Börnke, Frederik; Ruppel, Silke (Frontiers in Plant Science, 2017)
Endophytic plant growth-promoting bacteria have significant impact on the plant physiology and understanding this interaction at the molecular level is of particular interest to support crop productivity and sustainable production systems. We used a proteomics approach to investigate the molecular mechanisms underlying plant growth promotion in the interaction of Kosakonia radicincitans DSM 16656 with Arabidopsis thaliana. Four weeks after the inoculation, the proteome of roots from inoculated and control plants was compared using two-dimensional gel electrophoresis and differentially abundant protein spots were identified by liquid chromatography tandem mass spectrometry. Twelve protein spots were responsive to the inoculation, with the majority of them being related to cellular stress reactions. The protein expression of 20S proteasome alpha-3 subunit was increased by the presence of K. radicincitans. Determination of proteasome activity and immuno blotting analysis for ubiquitinated proteins revealed that endophytic colonization interferes with ubiquitin-dependent protein degradation. Inoculation of rpn12a, defective in a 26S proteasome regulatory particle, enhanced the growth-promoting effect. This indicates that the plant proteasome, besides being a known target for plant pathogenic bacteria, is involved in the establishment of beneficial interactions of microorganisms with plants.